The Efficacy of Lactobacillus plantarum as Adjunctive Therapy of Bacterial Vaginosis: A Double-blind, Randomized, Placebo-controlled Trial - Ridha Ramadina Widiatma; Muhammad Yulianto Listiawan; Dwi Murtiastutik; Cita Rosita Sigit Prakoeswa; Sawitri Sawitri; Ingrid Suryanti Suryono; Linda Astari; Afif Nurul Hidayati (Faculty of Medicine, Universitas Airlangga, 2020)
Background: Bacterial vaginosis (BV) is a clinical syndrome caused by the changing of Lactobacillus spp., a producer of hydrogen peroxide, in the normal vagina with a high concentration of anaerobic bacteria, Gardnerella vaginalis and Mycoplasma hominis. This study reports a resistance of BV therapy regimens, high recurrence rates, and side effects of an antibiotic. Therefore, adjunctive therapy for BV management is needed. Research has reported the therapeutic effects of probiotic in BV; however, the results are inconsistent. Purpose: To evaluate the efficacy of standard therapy using metronidazole and Lactobacillus plantarum for BV measured by the cure rate and vaginal flora balance. Methods: A randomized, double-blind, placebo-controlled trial, 30 subjects were randomized to take metronidazole 500 mg twice a day for seven days with weekly evaluation. The Lactobacillus plantarum or placebo group was evaluated every 4 weeks. The cure rate and vaginal flora balance were evaluated using the Amsel criteria and Nugent score before and after the intervention. Result: A total of 30 subjects returned for 28-day follow-up, of which 60% subjects of the antibiotic/probiotic group were cured compared to 40% in the antibiotic/placebo group (p>0.05). Conclusion: There was no difference in the increase of cure rate and vaginal flora balance between the treatment group and significant control group.